2016
DOI: 10.1002/ange.201602252
|View full text |Cite
|
Sign up to set email alerts
|

Annulation of Alkynyl Aryl Ethers with Allyl Pivalates To Give 2,3‐Bismethylenechromanes through Double C−H Bond Cleavage

Abstract: The treatment of silylethynyloxyarenes with allylic pivalates in the presence of apalladium catalyst led to efficient CÀHbond cleavage in both substrates and anovel annulation reaction to give 2,3-bismethylenechromanes.W hen orthoallylated silylethynyloxybenzenes were used as the substrates, the same products were obtained. This result shows that siteselective intramolecular hydrovinylation is involved in the annulation reaction. The synthetic utility of the products was demonstrated by the construction of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 113 publications
1
3
0
Order By: Relevance
“…In particular, the allylic pivalate containing a tert-butyl or trifluoromethyl group underwent the annulation with p-anisyl triisopropylsilylethynyl ether to give the corresponding cycle (Scheme 4). 19 The higher energy barrier computed for the trifluoromethylated product with respect to the product containing a tert-butyl group [3.7 kcal/mol (see Table 2)] is in nice agreement with the past experimental yields reported in Scheme 4. 16…”
Section: ■ Results and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In particular, the allylic pivalate containing a tert-butyl or trifluoromethyl group underwent the annulation with p-anisyl triisopropylsilylethynyl ether to give the corresponding cycle (Scheme 4). 19 The higher energy barrier computed for the trifluoromethylated product with respect to the product containing a tert-butyl group [3.7 kcal/mol (see Table 2)] is in nice agreement with the past experimental yields reported in Scheme 4. 16…”
Section: ■ Results and Discussionsupporting
confidence: 84%
“…18 Recently, Minami et al demonstrated that aryl (TIPS)ethynyl ethers undergo double C−H bond-cleaving annulation with allylic pivalates in the presence of Cs 2 CO 3 (base) and a palladium catalyst at a high temperature (140 °C), leading to 2,3-bismethylenechromanes (Scheme 2). 19 For this reaction, decreasing the reaction temperature provided only lower yields, finding no isomeric products. Overall, the associated reaction pathway can be divided into two sections: the ortho allylation of aryl ethynyl ethers via ortho-C−H bond activation and the intramolecular hydrovinylation of the alkynyl groups with the connected alkenyl group.…”
Section: ■ Introductionmentioning
confidence: 91%
“…In 2016, Hiyama and co-workers reported the annulation of alkynyl aryl ethers via double C-H bond activation and intramolecular hydrovinylation through vinylic C-H bond cleavage to produce synthetically useful 2,3-bismethylenechromanes (Scheme 13A). 66 Notably, arenes bearing electron-releasing group proved to be more effective. meta-Substituted arenes offered a mixture of products showing lack of regioselectivity.…”
Section: Allyl Pivalatesmentioning
confidence: 99%
“…However,n ot race of the desired exo-insertion product was detected, [2g-i] suggesting that different conditions were required. Gratifyingly,w eh ad a strategy for aryl alkynyl ethers to provide av ariety of oxacycles via CÀHb ond activation, [11] including hydroalkylation via ali-phaticC ÀHb ond activation under Pd 0 /acid-catalyzed conditions. [11d] We found that exo hydroarylationo f1a proceeded in the presenceo fP d(dba) 2 (5 mol %), PCy 3 (5 mol %), and pivalic acid (10 mol %) at 100 8Ci nt oluene to give bismethylenedihydrobenzofuran 2a in 77 %y ield as as tereoisomeric mixture at the C3 silylmethylidene moiety (Table 1, entry 1).…”
mentioning
confidence: 99%